Analisis Strategi Pemasaran Untuk Meningkatkan Penjualan Pada Perusahaan NU Bodyshop Paiton Probolinggo - Zaenori, Zaenori (Fakultas Sosial dan Humaniora, 2023)
NU Bodyshop is a start-up company engaged in cosmetics in Pondok Kelor Paiton Probolinggo. As a start-up company that has many competitors, NU Bodyshop has experienced many challenges and obstacles, so that its product sales have not increased significantly or been stagnant. From the problems mentioned above, it is the main attraction for the author to examine more deeply in the form of scientific work (thesis) with the object of the marketing strategy that has been applied to the NU Bodyshop Paiton Probolinggo. The purpose of this research is to find out the marketing strategy applied by NU Bodyshop Paiton Probolinggo in increasing sales of its products. To answer these problems a qualitative descriptive approach is used using SWOT analysis to take advantage of opportunities, maximize strengths, reduce weaknesses and avoid threats with data collection techniques through observation, interviews and documentation. The results of the study using the SWOT analysis, it can be seen that the NU Bodyshop Paiton Probolinggo is implementing a SO (Strenght-Opportunity) Strategy, namely a strategy in which the company uses its strengths and opportunities to run its business. Thus NU Bodyshop Paiton Probolinggo should concentrate on maintaining product quality, as well as improving service to consumers to get customers who are more loyal and remain creative in product innovation and use technology effectively in conducting promotions to expand the marketing network.